Effect of different acupuncture and moxibustion methods on functional dyspepsia caused by sequelae of COVID-19: A protocol for systematic review and meta-analysis. Issue 38 (23rd September 2022) - Peng, Tianzhong; Huang, Xuedi; Zhu, Manhua; Hou, Xinju; Xiong, Yue; Fang, Xinyue; Lin, Zitong; Liu, Lu; Lan, Wanning; Lin, Xingzhen
Abstract : Background: Functional dyspepsia (FD) is a group of diseases that cannot be explained after routine clinical examination, and is characterized by postprandial fullness, early satiety, and upper abdominal pain or burning. According to the statistics, FD continues to become one of the high-risk sequelae of coronavirus disease 2019 (COVID-19), affecting patients' quality of life, increasing psychological burden and increasing economic costs. However, its optimal treatment is still an urgent problem. A large number of studies have shown that acupuncture and moxibustion is effective and safe in the treatment of FD caused by sequelae of COVID-19, which is of research value. Therefore, based on the current literatures, the effectiveness and safety of different acupuncture and moxibustion methods were systematically evaluated to provide possible alternative therapy on FD. Methods: Studies search for eligible randomized controlled trials that use different acupuncture and moxibustion methods as the sole treatment on FD and their data extraction will be done by 2 researchers. In case of disagreement, a third researcher will be introduced for arbitration. Mean difference or relative risk with fixed or random effect model in terms of 95% confidence interval will be adopted for the data synthesis. To evaluate the risk of bias, the Cochrane risk of bias assessment tool will be utilized. The sensitivity or subgroup analysis will also be conducted when meeting high heterogeneity ( I 2 > 50%). Results: This meta-analysis will provide an authentic synthesis of different acupuncture and moxibustion methods on FD caused by sequelae of COVID-19. Conclusion: This meta-analysis will evaluate the effect of acupuncture and moxibustion on FD caused by sequelae of COVID-19, providing evidence as to the treatment in these patients.